A cross layer analysis for voice over WiFi communications in multihop wireless networks. (28th February 2008) - Stewart, Robert; Xiaoguang, Li; Schormans, John A.; Hasib, Maheen
The selection of appropriate inputs, which capture the variability in the traffic for the cross layer optimisation process, is the main problem to be addressed in this paper. This paper proposes enhanced probing and analytical techniques to obtain reliable network performance results in multihop networks. These results could be used as inputs to perform cross-layer analysis and QoS monitoring in multihop wireless networks. The issues highlighted are the possibly erroneous use of deterministic inputs in developing model formulations during the cross layer design process in multihop wireless networks based on 802.11e/s standards. These issues are explored and recommendations suggested which would be useful to industry in the performance evaluation and deployment of new applications such as Voice over WiFi (VoWiFi).